Literature review on teachers’ mindsets, growth-oriented practices and why they matter - Laine, Sonja; Tirri, Kirsi (Frontiers in Education, 2023)
This literature review focuses on earlier research on teachers' mindsets, i.e., teachers' implicit beliefs about the malleability of basic human qualities such as intelligence. More specifically, the review focuses on what teachers' mindsets are, how teachers' mindsets manifest in the teaching, studying, and learning process, how teachers' mindsets and growth-oriented practices are related to students' mindsets and learning, and how teachers' mindsets can be developed. Three electronic databases and backtracking references were used to search articles published between the years 2012 and 2023. After evaluating the eligibility of the articles, 64 were finally included in the review. The findings indicated that teachers' mindsets and growth-oriented practices matter. Most earlier research has found some kind of connection between teachers' mindsets and growth-oriented practices, and/or students' mindsets and learning. The implications for teacher education, policy, and future research are discussed.